Keanekaragaman Ikan yang Bernilai Ekonomi dan Kandungan Logam Berat Pb dan Cd pada Ikan Sapu-Sapu di Sungai Bedadung Jember - Munandar, Kukuh; Eurika, Novy (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
Water of river Bedadung in urban areas used by the local community for bathing, washing and toilet, and dispose of garbage and waste can be observed during the dry season. Whereas water of river Bedadung used by the Regional Water Company (PDAM) Jember as a raw water source in the areaÂ  ofÂ  Villa Tegal Besar estate District of Kaliwates. Besides the existing fish used for consumption by the public, both for their own consumption or for sale. The qualitative research with quantitative descriptive design. Location of research conducted by purposive sampling, the location of sampling carried out on three stations, namely: 1) Station 1 is located around the bridge Jl. Mastrip District of Sumbersari, 2) Station 2 is located in the vicinity of the bridge Jl. Ahmad Yani District of Sumbersari (or better known as the bridge "Gladak Twins", and 3) Station 3 located around the road bridge Imam Bonjol District of Kaliwates. Sampling was conducted in October 2015.The content of heavy metals Pb and Cd in fish brooms with AAS test, then the results compared with a maximum limit of heavy metal contamination in food in ISO 7387: 2009.The fish were caught as many as five types: fish â€œSapu-sapuâ€ (Hypostomus plecostomus), â€œNilaâ€ (Oreochromis niloticus), â€œLunjar Pariâ€ (Rasbora argyrotaenia), â€œWaderâ€ (Puntius brammoides), and Goldfish Comet (Carassius auratus). Based on the analysis with AAS test can be concluded that the Hypostomus fish caught in the river Bedadung on October 1, 2015 the average contains heavy metals amounted to 0.2563 ppm Pb and Cd of 0.172 ppm.